Romanipe on every road - Popović Nikolić, Danijela (Sociološki pregled, 2024)
Various phenomena from the field of Roma people’s culture encourage Romologists to conduct scientific studies, particularly those which would contribute to new findings in the sphere of intercultural relations and the recent status of spiritual manifestations. This paper elaborates the results of the research presented at the scientific gathering organized by the Serbian Academy of Sciences and Arts and published in the collection entitled Contribution of the Roma to the Culture of the People in Serbia. The researchers dedicate special attention to modern phenomena in different fields of spiritual culture: literature, music, language, forms of cultural organization etc.
Keywords: Roma; culture; intercultural relations; music; literature